Investigation of Multi Bypass Pulse Tube Cryocooler. (April 2019) - Shilledar, A; Patil, A; Atrey, M D
Abstract: To meet the growing demands of vibration free and compact cooling devices for various space and military based application, Pulse tube cryocoolers (PTC) are in focus. Several modifications have been attempted in recent past to increase the performance of the PTC. These includes different geometric configurations, phase shift mechanism, multi-staging, multi-bypass etc. Multi bypass PTCs (MBTC) are capable of achieving temperatures below 18 K, which could otherwise be achieved only by multi-stage configuration. The present work focuses on investigation of single bypass pulse tube cryocooler. Sage model is developed for single stage inline PTC without and with the bypass to study the influence of design parameters on cold end temperature. Experiments are carried out on new MBPTC and the results are compared with the predictions.